Evaluasi Kesuburan Tanah pada Berbagai Penggunaan Lahan di Kecamatan Tikung Kabupaten Lamongan: Soil Fertility Evaluation on Various Land Uses in Tikung District, Lamongan District - Rashif Hamzah, Hifzan; Sasongko, Purnomo Edi; Purwadi, Purwadi (Agrocentrum, 2024)
Evaluation of land capability is an effort to utilize land according to its potential. Land potential assessment is very necessary in the context of formulating policies, utilizing and managing land in a sustainable manner. This research aims to determine and evaluate the status of soil fertility in the use of paddy fields and fields in Tikung District based on land map units. survey method by taking samples in Tikung sub-district at a depth of 0-20 cm and 20-40 cm to test the physical and chemical properties of the soil, apart from also carrying out slope analysis in the field. The parameters used are texture, permeability, C-Organic, pH, K-dd, KB and phosphorus. Soil fertility status is based on soil analysis and determination using the Soil Fertility Index method (Technical Guidelines for Chemical Analysis of Soil, Plants, Water and Fertilizer 2023 Edition), in Tikung District, Lamongan Regency, it is classified as low soil fertility status